A Implementation of the National Health Insurance (JKN) Mobile Applicationin Sinjai Regency - Mutmainna Ramadani, Ria; Muhammad Takdir; Muhammad Lutfi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
This research discusses the implementation of the JKN Mobile application in Sinjai. Social security administering body (BPJS). The JKN Mobile application was launched by BPJS Health with the aim of providing maximum service to the community/participants. The aim of this research is to examine how the JKN Mobile application is implemented in providing health services in Sinjai Regency for the community/participants to use applications that facilitate online services. This research method uses a qualitative method with a case study approach with data collection techniques using literature studies and interviews. This research shows that the implementation of the JKN Mobile application in Sinjai Regency has not been optimal. There are several inhibiting factors in implementing the JKN Mobile application in Sinjai Regency, namely that the community is not fully aware of the use of the JKN Mobile application, as well as the lack of adequate facilities such as cellphones and networks. Therefore, it can be said that the implementation of the JKN Mobile application for the community/participants in Sinjai Regency has not gone completely well.